2022
DOI: 10.1039/d2ra03484k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics under pressure of gold nanoparticle supracrystals: the role of the soft matrix

Abstract: The bulk modulus of 3D FCC supracrystals of spherical gold nanoparticles is determined using high pressure-SAXS measurements. The organic ligand shell is found to be less compressible than pure dodecane with the same chain length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…First a low pressure series, below 10 GPa, aimed at comparing mechanical behavior such as bulk modlulus of different structure of supercrystals: FCC, BCC and C14. This complete our study previously published 22 on FCC structure in a pressure range where no structural transition is expected. The second series of experiments went up to 45 GPa, to extend our study to eventual structural transition or coalescence as reported in other NPs.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…First a low pressure series, below 10 GPa, aimed at comparing mechanical behavior such as bulk modlulus of different structure of supercrystals: FCC, BCC and C14. This complete our study previously published 22 on FCC structure in a pressure range where no structural transition is expected. The second series of experiments went up to 45 GPa, to extend our study to eventual structural transition or coalescence as reported in other NPs.…”
Section: Resultssupporting
confidence: 84%
“…The same reasoning can be made with C14 structure, resulting in the hierarchy of bulk modulii: B 0 matrix (BCC) > B 0 matrix (FCC) > B 0 matrix (C14). The fit using the Rault's model gives for the supercrystal: B 0 SC (BCC) = 8.5 ± 1 GPa, B 0 SC (FCC) = 5.3 ± 1 (as reported in our previous experiment 22 ), B 0 SC (C14) = 3 ± 1 GPa. and for the matrix: B 0 matrix (BCC) = 7 ± 1 GPa, B 0 matrix (FCC) = 4 ± 1 Gpa, B 0 matrix (C14) = 1.5 ± 1 GPa.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations